Oral Azithromycin Versus Doxycycline in the Treatment of Children With Uncomplicated Scrub Typhus: A Randomized Controlled Trial. Issue 3 (28th December 2021) - Kabir, Karthika I.; John, Joseph; Satapathy, Amit Kumar; Sahu, Suchanda; Behera, Bijayini; Padhy, Biswa Mohan
Abstract : Objectives: To compare the efficacy of azithromycin versus doxycycline in treatment of children with uncomplicated scrub typhus in terms of percentage of children who attained remission of fever after 72 hours of administration of first dose of the study drug, mean time taken to attain fever defervescence, normalization of laboratory parameters, resolution of hepatosplenomegaly and lymphadenopathy. Design: Interventional, open-labeled randomized controlled trial. Study methods: Patients admitted with undifferentiated fever in the In-Patient Department (IPD), Department of Paediatrics, All India Institute of Medical Sciences, Bhubaneswar, India, as per the inclusion criteria were randomized and was treated with azithromycin at 10 mg/kg/d in one group and doxycycline at 4.4 mg/kg/d for 5 days in the other group and was assessed based on the primary and secondary objectives. Results: There was no statistically significant difference between the percentage of children who attained remission of fever after 72 hours of administration of azithromycin (98.2%) and doxycycline (96.5%) ( P value 0.47) and the average time taken for fever defervescence (azithromycin: 24.53 hours; doxycycline: 25.82 hours; P value 0.36). The odds of attaining fever remission in the doxycycline group as compared with the azithromycin group was 1.01 (95% confidence interval −0.60 to −1.71), which was also statistically not significant. There was less incidence of adverse drug events in the azithromycin group (1.78%) as compared with the doxycycline group (8.6%), which was statistically significant ( P value 0.02). Conclusion: Azithromycin is equally efficacious in terms of fever defervescence, resolution of clinical signs and laboratory parameters as doxycycline, is safer and better tolerated in children.